Waste-Stream Management Optimization in Long-Duration Crewed Space Missions - Anih, Samuel Igbokwe (Department of Electrical Engineering, 2022)
Over the years, crewed space missions, starting from the first human spaceflight in 1961 to date, have adopted rudimentary strategies to manage waste-streams generated inside spacecraft. Currently, on the International Space Station (ISS), waste-streams are stowed for months and later loaded onto an outbound cargo vehicle for incineration in the Earth's atmosphere. But as humans start to move further away from low Earth orbit (LEO) in the future, the resupply of consumables and the management of waste-streams will become increasingly difficult due to the increasing distance from Earth and various constraints on crewed spacecraft. In such cases the ISS mode of waste-stream management would no longer be a suitable option as waste-streams generated would have to be managed within the spacecraft during the transit phase of those missions. Moreover, it would be imprudent to jettison unprocessed wastes out of airlocks, which would then potentially pose collision risks in certain orbits. Disposal on other celestial bodies would also potentially violate international guidelines for planetary protection. To address these future waste management challenges, first, a study of previous and current crewed space missions was performed to investigate and characterize their waste management strategies to understand the various techniques implemented with possible relevance to future long-duration crewed space mission scenarios. Secondly, the Waste for Energy and Volume Recovery (WEVR) campaign, which is predicated on waste management during future long-duration crewed space missions beyond low Earth orbit, was proposed and performed at the Institute of Space Systems (IRS) of the University of Stuttgart as part of the collaboration with the University of Cape Town's SpaceLab. The campaign designed and carried out decomposition experiments for two waste simulants conducted using an inductively heated plasma generator (IPG) with oxygen and nitrogen operational gases. The results from this work indicate that strategies implemented for previous and current crewed space mission waste management would not be suitable for missions further into the solar system due to the absence of substantial atmosphere similar to Earth's for waste disposal during the transit phases of the missions and at potential destinations for human exploration. The findings from the decomposition experiments also show that high enthalpy inductively heated plasma generators operated with the appropriate operational gases such as oxygen or nitrogen used in the WEVR campaign could decompose waste streams generated by astronauts during long-duration crewed space missions while generating useful products.